Pengaruh PBL Terhadap Keterampilan Generik Sains Siswa Pada Materi Larutan Elektrolit dan Non Elektrolit - Dwi Retno Sari; Ratu Evina Dibyantini (Universitas Negeri Medan, 2019)
This study aims to determine the effect of problem-based learning model (PBL) on students' generic science skills in electrolyte and non-electrolyte solution material. This research is an experimental research. The population in this study were all class X students of SMA Negeri 1 Lubuk Pakam. Sampling was done randomly by taking 2 classes, namely one experimental class (PBL model) and one control class (DI model). The instruments used in the form of objective tests in the form of multiple choices amounted to 20 questions and essay questions to measure students' critical thinking skills as many as 5 questions. Homogeneous and normal data were analyzed by paired sample t-test and N-gain normalized using SPSS Version 20. The results showed that there was an influence of PBL learning models on students' generic science skills in electrolyte and non-electrolyte solution materials. The generic skills of direct observation science are the most developed generic science skills while the lowest generic science skills are symbolic language.